The Effect of Problem-Based Learning with Student Worksheets on Senior High School Students’ Higher Order Thinking Skill and Physics Learning Outcomes - Inayatus Soleha; Singgih Bektiarso; Subiki Subiki (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2022)
Implementation of the 2013 curriculum where students are trained to participate in student-centered learning and have higher-order thinking skills. This research aimed to determine the effect of the problem-based learning model (PBL) assisted by worksheets on high-level thinking skills (HOTS) and high school students learning outcomes in physics. This research uses a quasi-experimental type with a post-test only control group design. The research population consisted of all 5 class X MIPA students, while the sample consisted of 68 respondents from 2 class X MIPA. Data collection was carried out by giving written tests, documentation, and interviews. The research data were analyzed through statistical tests with the SPSS application. Based on the research results, it was found that there was no significant effect on the application of the PBL model assisted by the worksheets High Order Thinking Skill (HOTS) and the learning outcomes of high school students in physics material with a sig value of > 0.05. The causative factors based on the results of the analysis are external factors and internal factors in online learning activities. Thus it is necessary to have good control over these constraints so that the application of models and media can practice HOTS abilities and students' physics learning outcomes.